Credit Rating for Small and Medium Enterprises: Problems and Prospects in Bangladesh - Anwar, S. M Rakibul (Journal of Asian Business Strategy, 2017)
Small and Medium Enterprises (SMEs) are contributing in economic development worldwide. Research shows that the main challenge for getting loans is information asymmetry between external creditors and SMEs themselves. This makes SMEs investment more risky and vulnerable for the investors. In this situation, credit rating agencies play an important role by rating the SMEs that reflects overall creditworthiness of the SMEs. The aim of this paper is to identify major problems and prospects of SMEs financing and comparative rating process of SMEs in Bangladesh. Presently, credit rating agencies in Bangladesh follow the similar process as in Japan and India. A major problem arises because rating fees is the key source of revenue for credit rating agencies which infuses a conflict of interest of marking high ratings. Moreover, Bangladesh still could not establish institutions which exists in developed countries e.g., Credit Guarantee Corporations (CGC) that supports SMEs as a credit guarantor in Japan. Apart from this, Bangladesh government may encourage boosting investor pay or subsidized model (this is at practice in India) that increases SMEs rating.